2014
DOI: 10.1002/clc.22324
|View full text |Cite
|
Sign up to set email alerts
|

Noncardiac Surgery in Patients With Aortic Stenosis: A Contemporary Study on Outcomes in a Matched Sample From the Danish Health Care System

Abstract: BackgroundPast research has identified aortic stenosis (AS) as a major risk factor for adverse outcomes in noncardiac surgery; however, more contemporary studies have questioned the grave prognosis. To further our understanding of this, the risks of a 30‐day major adverse cardiovascular event (MACE) and all‐cause mortality were investigated in a contemporary Danish cohort.HypothesisAS is not an independent risk factor for adverse outcomes in noncardiac surgery.MethodsAll patients with and without diagnosed AS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Among the common urgent-emergent non-cardiac surgical procedures, hip fracture treatment has a prominent epidemiologic role. The incidence of severe AS in patients who need surgery for hip fracture is between 5% and 10% 6. Although after hip surgery 30-day mortality in severe AS is between 7% and 14%,7–9 these data may be an underestimate since the diagnosis of AS is not uncommonly missed before surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Among the common urgent-emergent non-cardiac surgical procedures, hip fracture treatment has a prominent epidemiologic role. The incidence of severe AS in patients who need surgery for hip fracture is between 5% and 10% 6. Although after hip surgery 30-day mortality in severe AS is between 7% and 14%,7–9 these data may be an underestimate since the diagnosis of AS is not uncommonly missed before surgery.…”
Section: Introductionmentioning
confidence: 99%
“…37-40 A more recent analysis, which included both asymptomatic and symptomatic patients, showed that 30-day mortality to be 3.8%, which was only slightly higher than aged matched controls (2.9%). 41 When looking exclusively at asymptomatic AS, other retrospective studies showed no difference in 30-day mortality but revealed higher composite major adverse cardiac events and nonlethal MI. 42,43…”
Section: Risk Stratification For Noncardiac Surgerymentioning
confidence: 98%
“…15 AS was identified based on diagnostic codes, and was not quantified. There was no difference in allcause mortality (3.8% in AS patients vs. 2.9% in controls, p=0.19) or a combined end-point (cardiovascular death, non-fatal myocardial infarction, ischemic stroke; 3.7% vs 2.9% in controls, p=0.13).…”
Section: Contemporary Reportsmentioning
confidence: 99%